Benzylation of acetic acid to benzyl acetate over highly active and reusable micro/meso-HZSM-5 - Nandiwale, Kakasaheb Y.; Galande, Nitish D.; Raut, Sunil A.; Bokade, Vijay V. (Chemical Engineering Research & Design, 2015)
Catalytic benzylation of acetic acid (AA) with benzyl alcohol (BA) to benzyl acetate was studied over zeolites viz. H-ZSM-5 (microporous, medium pore), Micro/Meso-HZSM-5 (combination of micro- and meso pore), H-Beta (microporous, large pore) to investigate catalytic activity and selectivity towards benzyl acetate. Micro/Meso-HZSM-5 obtained by desilication post-treatment has been employed as a heterogeneous catalyst for benzylation reaction probably for the first time. Micro/Meso-HZSM-5 was found to be a promising catalyst for benzylation with AA conversion of 94%, selectivity towards benzyl acetate of 95%. The detailed optimization of process parameters such as molar ratio, catalyst loading, reaction temperature and time was also presented. Micro/Meso-HZSM-5 catalyst was observed to be stable for six cycles (1 fresh and 5 recycles). The first order reaction kinetics (R-2 >0.98) indicated that reaction rate constants increased with increasing reaction temperature. The activation energy for benzylation of AA with BA over Micro/Meso-HZSM-5 was obtained to be 15.07 kJ mol(-1), which is far less than the reported. (C) 2014 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Acetic acid; Benzyl acetate; Benzyl alcohol; Benzylation; Micro/Meso-HZSM-5; Reaction kinetics

Binderless low silica X zeolite for methane separation from binary CO2/CH4 biogas stream: A comprehensive experimental and computational study - Yadav, Tushar R.; Shrotri, Aadesh R.; Kate, Pranjali N.; Devasia, George; Niphadkar, Prashant S.; Mali, Nilesh A.; Krishnamurty, Sailaja; Bokade, Vijay V.; Nandanwar, Sachin U. (Journal of Industrial and Engineering Chemistry, 2025)
This study presents the synthesis of binderless Na-LSX (B-Na-LSX) and binderless NaK-LSX (B-NaK-LSX). XRD, SEM, EDS, and N-2 physisorption were used for characterization of samples. Computational modelling of prepared sorbent was performed for the fundamental understanding of zeolite topology and adsorption behaviour. The breakthrough experiments are used to evaluate the adsorption capacities on CO2/CH4 (40/60 vol%) binary biogas stream. The results were compared with commercial Na-LSX (C-Na-LSX). The breakthrough adsorption capacity of B-Na-LSX was 3.08 mmol g(-1) and 0.29 mmol g(-1) of CO2 and CH4, respectively, at 300 K and 1 bar. CO2 sorption capacity of B-Na-LSX was similar to 11 % and similar to 17 % higher than B-NaK-LSX (2.77 mmol g(-1)) and C-Na-LSX (2.56 mmol g(-1)), respectively. DFT study reveals that the higher adsorption of CO2 over CH4 was attributed to higher charge transfer from CO2 to zeolite framework. Dual-bed six-step Pressure Swing Adsorption (PSA) was performed on B-Na-LSX at 6 bar. similar to 232 cycles were run with above 98 % of CH4 purity and similar to 74 % of recovery. The life-cycle test of sorbent was studied. It was implied that the designed sorbent is effective to produce the high purity of CH4 and can be utilized for a longer period for CH4 production.
Keywords: Binderless; Biogas; LSX zeolite; methane; PSA; Separation